Complete molar pregnancy in adolescents from North and South America: Clinical presentation and risk of gestational trophoblastic neoplasia - Soares, Renan Rocha [UNESP]; Maestá, Izildinha [UNESP]; Colón, José; Braga, Antonio; Salazar, Aleydah; Charry, Rafael Cortés; Sun, Sue Yazaki; Goldstein, Donald P.; Berkowitz, Ross S. (Elsevier, 2016)
Objectives To compare complete hydatidiform mole (CHM) clinical presentation and risk factors associated with GTN development between North American and South American adolescents. Methods This non-concurrent cohort study was undertaken including adolescents with CHM referred to centers in North America (New England Trophoblastic Disease Center, Harvard University, USA), and South America (Botucatu Trophoblastic Disease Center-São Paulo State University, Brazil; Trophoblastic Unit of Central University of Venezuela and Maternidad Concepcion Palacios of Caracas, Venezuela) between 1990 and 2012. Data were obtained from medical records and pathology reports. Study participants were allocated into 2 groups: North America (NA) and South America (SA). Results In NA and SA, 13.1% and 30.9% of patients with hydatidiform mole were adolescents, respectively. Of these, 77.6% in NA and 86.1% in SA had pathologic diagnosis of CHM (p = 0.121). Vaginal bleeding (SA = 69% vs NA = 51%; p = 0.020), anemia (SA = 48% vs NA = 18%; p < 0.001), and elevated serum hCG (SA = 232,860 mIU/mL vs NA = 136,412 mIU/mL; p = 0.039) were more frequent in SA than in NA. Median gestational age at diagnosis (SA = 12 weeks, NA = 11 weeks; p = 0.030) differed whereas GTN development rate (SA = 20%, NA = 27%; p = 0.282) showed no significant difference between groups. Compared to NA, medical complications and clinical factors associated with post-molar GTN were more frequent among SA adolescents. Conclusions Medical complications and clinical factors associated with GTN development were more frequent in SA than in NA adolescents with CHM, suggesting that, in South America, awareness about the importance of diagnosing molar pregnancy early and considering CHM in the differential diagnosis in adolescents suspected to be pregnant should be raised.
Keywords: Adolescents; Gestational trophoblastic neoplasia; Molar pregnancy